Indoor Localization of a Quadrotor Based on WSN: A Real-Time Application. (17th January 2013) - Rullan-Lara, Jose L.; Sanahuja, Guillaume; Lozano, Rogelio; Salazar, Sergio; Garcia-Hernandez, Ramon; Ruz-Hernandez, Jose A.
A real-time localization algorithm is presented in this paper. The algorithm presented here uses an extended Kalman filter and is based on Time Difference Of Arrivals (TDOA) measurements of radio signal. The position and velocity of an Unmanned Aerial Vehicle (UAV) are successfully estimated in closed-loop in real-time, both in hover and path following flights. Relatively small position errors obtained from the experiments prove the good performance of the proposed algorithm.